Management of coronary artery disease in a Tertiary Care Hospital - Wal, Pranay (Medknow Publications & Media Pvt Ltd, 2013)
AIMS: The objective of the study was to study the prescribing patterns of drugs used in the coronary artery disease (CAD) and to identify, which drug is mostly prescribed at that hospital. SETTINGS AND DESIGN: This was a prospective observational survey including case series analysis of patients with CAD who met the inclusion criteria. It was conducted in the cardiology unit of multidisciplinary Tertiary Care Hospital in Kanpur. MATERIALS AND METHODS: Data of patients who met the inclusion criteria was collected in specially designed case record forms. It was designed to include the patient data such as, demographics, risk factors, clinical and biochemical characteristics, procedures and investigations performed during the hospital stay, in-hospital and discharge drug therapy. STATISTICAL ANALYSIS USED: Descriptive statistics were performed for baseline characteristics, risk factors and medication use. All the analyses were performed using Statistical Package for Social Sciences version 16.0. RESULTS: Subjects of age groups 65-74 (33.34%) were found to be more susceptible to CAD. In this study, we see that Aspirin, Clopidogrel and Statins were mostly prescribed in this hospital. CONCLUSIONS: In this study, Aspirin and Clopidogrel were mostly prescribed. According to 2009 focused updates of American College of Cardiology/American Heart Association (ACC/AHA) guidelines for the management of patients with ST-elevation Myocardial Infarction. So in this hospital prescription for CAD were according to the guideline.